Effectiveness of Instagram Sponsored as Advertising/Promotion Media (Study of Tiket.com Advertisement with EPIC Model Method) - Nabila Amira; Iis Kurnia Nurhayati (Universitas Mataram, 2019)
The use of advertisements using social media is now increasingly widespread, one of which is Instagram social media. Instagram currently brings up the Instagram Sponsored feature as an alternative advertising medium. Tiket.com is one type of e-ticketing business in Indonesia and is actively promoting its advertising, one of which is by using Instagram Sponsored. This Instagram Sponsored feature is still fairly new as an advertising medium on Instagram media, so researchers want to measure the effectiveness of Instagram Sponsored feature advertising media through Tiket.com ads using the Instagram Sponsored feature with the A.C Nielsen EPIC method. This study uses a quantitative description methodology with the population of @tiketcom Instagram followers using four EPIC Model approaches namely Empathy, Persuasion, Impact, and Communication. The results of this study showed that the average EPIC rate score was 2.9, so it was declared effective.Keywords: Effectiveness, EPIC, Instagram Sponsored, Tiket.com